2019
DOI: 10.1021/acsenergylett.9b00788
|View full text |Cite
|
Sign up to set email alerts
|

Intercalation of Magnesium into a Layered Vanadium Oxide with High Capacity

Abstract: While α-V2O5 has traditionally been considered as a promising oxide to reversibly intercalate high levels of Mg2+ at high potential, recent reports indicate that previously observed electrochemical activity is dominated by intercalation of H+ rather than Mg2+, even in moderately dry nonaqueous electrolytes. Consequently, the inherent functionality of oxides to intercalate Mg2+ remains in question. By conducting electrochemistry in a chemically and anodically stable ionic liquid electrolyte, we report that, at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
99
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 83 publications
(114 citation statements)
references
References 46 publications
6
99
0
Order By: Relevance
“…Figure a displays the first galvanostatic charge/discharge profile of V 2 O 5 spheres that exhibit specific discharge capacity of 225 mA h g −1 with distinct and flat charge and discharge plateaus demonstrating significantly improved kinetics than previous reports. [ 26,37,43,46,47 ] Further in order to understand the charge/discharge mechanism, the differential capacity (d Q /d V ) is plotted versus voltage from the galvanostatic data (Figure 3b). During intercalation, two distinct peaks are observed that are positioned at ≈2.04 V (vs Mg/Mg +2 ) and ≈2.01 V (vs Mg/Mg +2 ), while during deintercalation, three peaks appear at 2.17 V (vs Mg/Mg +2 ), 2.18 V (vs Mg/Mg +2 ), and 2.20 V (vs Mg/Mg +2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Figure a displays the first galvanostatic charge/discharge profile of V 2 O 5 spheres that exhibit specific discharge capacity of 225 mA h g −1 with distinct and flat charge and discharge plateaus demonstrating significantly improved kinetics than previous reports. [ 26,37,43,46,47 ] Further in order to understand the charge/discharge mechanism, the differential capacity (d Q /d V ) is plotted versus voltage from the galvanostatic data (Figure 3b). During intercalation, two distinct peaks are observed that are positioned at ≈2.04 V (vs Mg/Mg +2 ) and ≈2.01 V (vs Mg/Mg +2 ), while during deintercalation, three peaks appear at 2.17 V (vs Mg/Mg +2 ), 2.18 V (vs Mg/Mg +2 ), and 2.20 V (vs Mg/Mg +2 ).…”
Section: Resultsmentioning
confidence: 99%
“…As a result, Nano ζ-V 2 O 5 possessed a higher energy density than Bulk ζ-V 2 O 5 (250 and 140 W h kg −1 , respectively, on the second cycle), which compares favorably with state-of-the-art sulfide materials such as Chevrel Mo 6 S 8 (77 W h kg −1 ), 10 Spinel Ti 2 S 4 (228 W h kg −1 ), 11 and oxides such as Mo 2.48 VO 9.93 (∼250 W h kg −1 ), 34 and MoO 3 (270 W h kg −1 ), 35 although it is still somewhat short of the highest energy density recorded for an oxide (α-V 2 O 5 , 660 W h kg −1 ). 15 Clearly, nanosizing ζ-V 2 O 5 increased its obtainable energy density by mitigating diffusive limitations on cycling kinetics. Unfortunately, the direct probing of Mg diffusion using standard techniques such as the Galvanostatic Intermittent Titration Technique (GITT) and Electrochemical Impedance Spectroscopy (EIS) are not yet suitable for these prototype systems, given the prevalent side reactions present between the electrodes and the electrolyte.…”
Section: Resultsmentioning
confidence: 99%
“…The active material loading of 60 wt%, while lower than typical loadings for Li-ion electrode testing, is common for Mg-ion testing given the sluggish reaction kinetics of Mg insertion and removal. 15,32,33 These were pressed (8 tons) and dried at 100°C overnight under vacuum in the glovebox antechamber. Cells that were cycled repeatedly, possessed active material loadings in the range 1.5 to 2.5 mg cm −2 , whereas charged or discharged electrodes used for postmortem analysis were in the range 0.7 to 1.5 mg cm −2 .…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
See 2 more Smart Citations